2012
DOI: 10.5194/acp-12-3799-2012
|View full text |Cite
|
Sign up to set email alerts
|

Variability of black carbon deposition to the East Antarctic Plateau, 1800–2000 AD

Abstract: Abstract. Refractory black carbon aerosols (rBC) from biomass burning and fossil fuel combustion are deposited to the Antarctic ice sheet and preserve a history of emissions and long-range transport from low-and mid-latitudes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 41 publications
3
48
2
Order By: Relevance
“…Mass concentrations of BC in snow and ice cores in Antarctica have been reported between 100 and 950 ng L −1 by optical analysis (Chýlek et al, 1992;Grenfell et al, 1994;Warren & Clarke, 1990) and between 30 and 1,300 ng L −1 by the SP2/Nebulizer system (Bisiaux, Edwards, McConnell, Albert, et al, 2012;Bisiaux, Edwards, McConnell, Curran, et al, 2012;Khan et al, 2018). Mass concentrations of BC in snow and ice cores in Antarctica have been reported between 100 and 950 ng L −1 by optical analysis (Chýlek et al, 1992;Grenfell et al, 1994;Warren & Clarke, 1990) and between 30 and 1,300 ng L −1 by the SP2/Nebulizer system (Bisiaux, Edwards, McConnell, Albert, et al, 2012;Bisiaux, Edwards, McConnell, Curran, et al, 2012;Khan et al, 2018).…”
Section: Bc Concentrations In Snow At the Syowa Stationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass concentrations of BC in snow and ice cores in Antarctica have been reported between 100 and 950 ng L −1 by optical analysis (Chýlek et al, 1992;Grenfell et al, 1994;Warren & Clarke, 1990) and between 30 and 1,300 ng L −1 by the SP2/Nebulizer system (Bisiaux, Edwards, McConnell, Albert, et al, 2012;Bisiaux, Edwards, McConnell, Curran, et al, 2012;Khan et al, 2018). Mass concentrations of BC in snow and ice cores in Antarctica have been reported between 100 and 950 ng L −1 by optical analysis (Chýlek et al, 1992;Grenfell et al, 1994;Warren & Clarke, 1990) and between 30 and 1,300 ng L −1 by the SP2/Nebulizer system (Bisiaux, Edwards, McConnell, Albert, et al, 2012;Bisiaux, Edwards, McConnell, Curran, et al, 2012;Khan et al, 2018).…”
Section: Bc Concentrations In Snow At the Syowa Stationmentioning
confidence: 99%
“…Studies have also analyzed both BC mass and number concentrations and size distributions of Denver fresh snow and Arctic snow , Sapporo snow (Ohata et al, 2013), Arctic snow Sinha et al, 2018), Alpine surface snow, Caucasus high-elevation firn, Greenland summit firn, and Himalayan surface snow (Lim et al, 2014). On the other hand, regarding the Southern Hemisphere, limited numbers of studies show the concentrations of BC in snow in Antarctica (Chýlek et al, 1987;Grenfell et al, 1994;Khan et al, 2018Khan et al, , 2019Warren & Clarke, 1990) and BC in ice core samples (Bisiaux, Edwards, McConnell, Albert, et al, 2012;Bisiaux, Edwards, McConnell, Curran, et al, 2012;Chýlek et al, 1992;McConnell et al, 2007). Recently, Khan et al (2018) reported the BC size distribution of snow samples in western Antarctica, but no study has been reported in eastern Antarctica.…”
Section: Introductionmentioning
confidence: 99%
“…Here we compared the past 150 years of BC for a suite of ice cores from Antarctica (Figures 8 and S6, Table 1), and we evaluated the measured fluxes against modeled BC flux [ Lee et al, 2013] to investigate temporal and spatial variations in BC fluxes. We compared the East Antarctic Law Dome record [Bisiaux et al, 2012a[Bisiaux et al, , 2012b, the West Antarctic Pine Island Glacier (PIG), Thwaites Glacier (THW) and the divide between Pine Island and Thwaites Glaciers (DIV) [Criscitiello et al, 2014] records, and the James Ross Island (JRI) record from the Antarctic Peninsula [Mulvaney et al, 2012;Arienzo et al, 2016]. approximately 1960 to the mid-1990s.…”
Section: Long-range Transportmentioning
confidence: 99%
“…Measurements of actual impurity concentrations in snowpacks and glaciers have been conducted on different spatial and temporal scales in natural conditions by for example Clarke and Noone (1985); McConnell et al (2007); Ming et al (2008); Xu et al (2009) ;Forsström et al (2009); Doherty et al (2010); Kaspari et al (2011);Bisiaux et al (2012); Meinander et al (2013); Svensson et al (2013); Dagsson-Waldhauserova et al (2015). Furthermore, to observe the effects of impurities on the snow, several experimental studies have been conducted (Conway et al, 1996;Brandt et al, 2011;Hadley and Kirchstetter, 2012).…”
Section: J I Peltoniemi Et Al: Reflectance Of Contaminated Snowmentioning
confidence: 99%